Vulvovaginal Atrophy - Mac Bride, Maire B. (Mayo Foundation for Medical Education and Research, 2010)
Vulvovaginal atrophy (VVA) is a common and underreported condition associated with decreased estrogenization of the vaginal tissue. Symptoms include dryness, irritation, soreness, and dyspareunia with urinary frequency, urgency, and urge incontinence. It can occur at any time in a woman's life cycle, although more commonly in the postmenopausal phase, during which the prevalence is close to 50%. Clinical findings include the presence of pale and dry vulvovaginal mucosa with petechiae. Vaginal rugae disappear, and the cervix may become flush with the vaginal wall. A vaginal pH of 4.6 or more supports the diagnosis of VVA. Even while taking systemic estrogen, 10% to 20% of women may still have residual VVA symptoms. Breast cancer treatment increases the prevalence of VVA because the surgical, endocrine, and chemotherapeutic agents used in its treatment can cause or exacerbate VVA. Local estrogen treatment for this group of women remains controversial.